Response of rhizosphere microbial community of Chinese chives under different fertilization treatments - Niu, Tianhang; Xie, Jianming; Li, Jing; Zhang, Jing; Zhang, Xiaodan; Ma, Hongyan; Wang, Cheng (Frontiers in Microbiology, 2022)
Soil microorganisms play an irreplaceable role in agricultural production; however, an understanding of the response of soil microorganisms to slow-release and common fertilizer applications is limited. In this study,we set up an experiment in a plastic greenhouse overwintering Chinese chives growing area to investigate the effects of no fertilization (control;CK),conventional fertilization (T1,NPK: 91.3kg667m-2),reduced fertilizer with slow-release fertilizer (T2,NPK:62.8kg667m-2),constant fertilizer with slow-release fertilizer (T3,NPK:91.3 kg 667m-2),and reduced application (T4,NPK:62.8kg667m-2) on rhizosphere soil physicochemical properties and soil microbial communities (bacteria and fungi) of Chinese chives were studied.We found that the application of slow-release fertilizer had a significant improvement in soil nutrients, soil enzyme activity and soil microbial community structure and diversity compared to conventional fertilizer application.The T2 treatment was the more effective. Compared with the T1 treatment, the content of total nitrogen(TN)and available phosphorus (AP) in the soil increased by 42.58% and 16.67%, respectively.The SU-E activity in the T2 treatment increased by 9.70% compared with T1.The 16s rRNA sequencing results showed that the soil bacterial diversity index increased after the slow-release fertilization compared with the conventional fertilization.The T2 treatment was more likely to increase the soil bacterial diversity index and improving the soil microbial community structure.The relative abundance of each species increased in the T2 treatment, such as Byssovorax, Sandaracinus, and Cellvibrio.The ITS sequencing results showed that soil fungal diversity, and the number of species decreased after fertilization.Compared with CK, the relative abundance of Ascomycota increased in each fertilization treatment.Further, the relative abundance of pathogenic fungi such as Pezizomycetes, Cantharellales, and Pleosporales decreased in the T2 treatment.PCoA analysis showed that both the amount of fertilizer applied and the type of fertilizer applied affected the soil microbial community structure.RDA evidenced that soil bacteria, Proteobacteria and Gemmatimonadetes, were closely correlated with soil AN, SOM, and AK. Acidobacteria were closely correlated with soil pH, TN, and AP. Ascomycota was closely correlated with soil pH and TN.In conclusion, the application of slow-release fertilizers and reduced fertilizer application can improve soil nutrient content, soil enzyme activity, soil microbial community structure and diversity, and contribute to sustainable soil development.Recommended fertilization rate for overwintering Chinese chives is NPK:62.8kg 667m-2.